2015
DOI: 10.1159/000431232
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Experience and Quality of Life in Children after Sport-Related Head Injuries: A Cross-Sectional Study

Abstract: Background: Sports are a major cause of concussions, and little is known about the symptom experience and health-related quality of life (HRQL) in children who remain symptomatic for over 3 months following such head injuries. Methods: A cross-sectional study of children aged 10-18 years was performed who were referred to the Neurosurgery Clinic at our centre following a head injury. Symptom experience was measured using the modified Concussion Symptom Scale, and HRQL was measured using the Pediatric Quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Our findings are supported by other studies that identified a negative impact on aspects of HRQOL following sport-related concussion 19 , 22 , 47 , 51 , 52 or mild traumatic brain injury 9 , 32 , 35 among children and adolescents. All but 1 of these investigations used patient-reported outcomes in evaluating HRQOL, which allows for standardization administration and measurement but does not necessarily take into account the relevance of the questions or additional meaning behind the lived experiences of the adolescents.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are supported by other studies that identified a negative impact on aspects of HRQOL following sport-related concussion 19 , 22 , 47 , 51 , 52 or mild traumatic brain injury 9 , 32 , 35 among children and adolescents. All but 1 of these investigations used patient-reported outcomes in evaluating HRQOL, which allows for standardization administration and measurement but does not necessarily take into account the relevance of the questions or additional meaning behind the lived experiences of the adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…Health-related quality of life (HRQOL) is a concept that considers the physical, psychological, and social aspects of one’s health and is defined by the individual’s experiences, beliefs, expectations, and perceptions of his or her ability to function in numerous domains of health and well-being. 45 Sport-related concussion symptoms and impairments can negatively influence aspects of HRQOL 19 , 22 , 32 , 35 , 47 , 52 , 60 and should be an important component of concussion assessment. As there is currently no patient-reported outcome measure for sport-related concussion, 49 researchers have used a combination of outcomes to assess aspects of HRQOL: generic (eg, Pediatric Quality of Life Inventory), 19 , 35 , 52 specific (eg, Beck Depression Inventory, Profile of Mood States), 20 , 23 , 27 and single item (eg, Global Rating of Change).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we observed a moderately strong correlation between symptoms and QOL ratings, extending work done among individuals of similar age to our sample (10-18 years) who presented to a specialty clinic for evaluation of persistent (>3 months) concussion symptoms and demonstrated reduced QOL in both psychosocial and physical health. 33 Collectively, prior work and the data from our investigation suggest that impairments in QOL following a concussion may serve as a marker to identify children and adolescents who should be further evaluated in a specialty concussion program. 13 Our study had some limitations and our findings should be interpreted in light of them.…”
Section: Discussionmentioning
confidence: 68%
“…For adolescent athletes, same day return to sports is not recommended regardless of full clinical recovery (4). It is important to recognize that some emotional or behavioral symptoms may persist for weeks to months even after full physical and cognitive recovery from concussion (32)(33)(34)(35).…”
Section: Outcome and Quality Of Lifementioning
confidence: 99%